Controllable Synthesis of 2D Nonlayered Cr2S3 Nanosheets and Their Electrocatalytic Activity Toward Oxygen Evolution Reaction - Shifa, Tofik Ahmed; Mazzaro, Raffaello; Morandi, Vittorio; Vomiero, Alberto (Frontiers in Chemical Engineering, 2021)
The design of oxygen evolution reaction (OER) electrocatalysts entirely based on Earth-abundant materials holds great promise for realizing practically viable water-splitting systems. In this regard, two-dimensional (2D) non-layered materials have received considerable attention in recent years owing to their intrinsic dangling bonds which give rise to the exposure of unsaturated active sites. In this work, we solved the synthesis challenge in the development of 2D non-layered Cr2S3 catalyst for OER application via introducing a controllable chemical vapor deposition scheme. The as-obtained catalyst exhibits a very good OER activity requiring overpotentials of only 230 mV vs RHE and 300 mV vs RHE to deliver current densities of 10 mA cm-2 and 30 mAcm-2 respectively with robust stability. This study provides a general approach to optimize the controllable growth of 2D non-layered material and opens up a fertile ground for studying the various strategies to enhance the water-splitting reactions.